Myocardial late gadolinium enhancement: prevalence, pattern, and prognostic relevance in marathon runners - Breuckmann, Frank; Möhlenkamp, Stefan; Nassenstein, Kai; Lehmann, Nils; Ladd, Susanne; Schmermund, Axel; Sievers, Burkhard; Schlosser, Thomas; Jöckel, Karl-Heinz; Heusch, Gerd; Erbel, Raimund; Barkhausen, Jörg (Radiology, 2009)
To prospectively analyze the myocardial distribution of late gadolinium enhancement (LGE) with delayed-enhancement cardiac magnetic resonance (MR) imaging, to compare the prevalence of this distribution in nonprofessional male marathon runners with that in asymptomatic control subjects, and to examine the prognostic role of LGE. Institutional review board and ethics committee approval were obtained for this study, and all subjects provided written informed consent. Two-dimensional inversion-recovery segmented k-space gradient-echo MR sequences were performed after administration of a gadolinium-containing contrast agent in 102 ostensibly healthy male runners aged 50-72 years who had completed at least five marathons during the past 3 years and in 102 age-matched control subjects. Predominantly subendocardial regions of LGE typical of myocardial infarction (hereafter, coronary artery disease [CAD] pattern) were distinguished from a predominantly midmyocardial patchy pattern of LGE (hereafter, non-CAD pattern). Marathon runners with LGE underwent repeat cardiac MR imaging and additional adenosine perfusion imaging. Runners were followed up for a mean of 21 months +/- 3 (standard deviation) after initial presentation. The chi(2), Fisher exact, and McNemar exact tests were used for comparisons. Event-free survival rates were estimated with the Kaplan-Meier method, and overall group differences were evaluated with log-rank statistics. Of the 102 runners, five had a CAD pattern of LGE, and seven had a non-CAD pattern of LGE. The CAD pattern of LGE was located in the territory of the left anterior descending coronary artery more frequently than was the non-CAD pattern (P = .0027, Fisher exact test). The prevalence of LGE in runners was higher than that in age-matched control subjects (12% vs 4%; P = .077, McNemar exact test). The event-free survival rate was lower in runners with myocardial LGE than in those without myocardial LGE (P < .0001, log-rank test). Ostensibly healthy marathon runners have an unexpectedly high rate of myocardial LGE, and this may have diagnostic and prognostic relevance.